2009
DOI: 10.2214/ajr.08.2005
|View full text |Cite
|
Sign up to set email alerts
|

Radioguided Localization of Nonpalpable Breast Cancer Lesions: Randomized Comparison With Wire Localization in Patients Undergoing Conservative Surgery and Sentinel Node Biopsy

Abstract: The radioguided technique is as effective as the standard wire technique for localization and excision of nonpalpable breast cancer lesions and is somewhat faster and simpler to perform than wire localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 33 publications
6
42
0
Order By: Relevance
“…Two RCTs are currently available, 22,23 but used power calculations that are based on an assumption of 15-20% reduction in involved margins favouring RGL. This percentage has been demonstrated to be unrealistic within these studies, 22,23 which identified no greater than a 7% difference favouring RGL and, therefore, failed to achieve statistical significance due to being statistically underpowered. Power calculations should be based on figures as low as 5-10% and subsequently larger sample sizes recruited to avoid this problem.…”
Section: Clinical Evidencementioning
confidence: 88%
See 4 more Smart Citations
“…Two RCTs are currently available, 22,23 but used power calculations that are based on an assumption of 15-20% reduction in involved margins favouring RGL. This percentage has been demonstrated to be unrealistic within these studies, 22,23 which identified no greater than a 7% difference favouring RGL and, therefore, failed to achieve statistical significance due to being statistically underpowered. Power calculations should be based on figures as low as 5-10% and subsequently larger sample sizes recruited to avoid this problem.…”
Section: Clinical Evidencementioning
confidence: 88%
“…All RCTs included in situ disease in their inclusion criteria, and in the randomization process the number of invasive and in situ lesions among patients who underwent wire-guided or radioguided localization did not differ significantly. [20][21][22][23]44,49,50 The small cohort sizes and the lack of power calculations for sample sizes also weakened the conclusions from these studies. 20,21,44,49,50 Despite the aforementioned limitations, a metaanalysis of the seven RCTs identified a significant difference between the two techniques, favouring use of RGL for shorter operating times (mean difference [MD] −2.95; 95% CI −4.43 to −1.47; P <0.0001), but at the expense of a significantly greater volume of tissue excised (MD 6.79; 95% CI 0.03−13.56; P = 0.05).…”
Section: Clinical Evidencementioning
confidence: 99%
See 3 more Smart Citations